Rapid mechanisms of glucocorticoid signaling in the Leydig cell - Hu, Guo-Xin (2007)
Stress-mediated elevations in circulating glucocorticoid levels lead to corresponding rapid declines in testosterone production by Leydig cells in the testis. In previous studies we have established that glucocorticoids act on Leydig cells directly, through the classic glucocorticoid receptor (GR), and that access to the GR is controlled prior to the GR by a metabolizing pathway mediated by the type 1 isoform of 11β-hydroxysteroid dehydrogenase (11βHSD1). This enzyme is bidirectional (with both oxidase and reductase activities) and in the rat testis is exclusively localized in Leydig cells where it is abundantly expressed and may catalyze the oxidative inactivation of glucocorticoids. The predominant reductase direction of 11βHSD1 activity in liver cells is determined by an enzyme, hexose-6-phosphate dehydrogenase (H6PDH), on the luminal side of the smooth endoplasmic reticulum (SER). Generation of the pyridine nucleotide cofactor NADPH by H6PDH stimulates the reductase direction of 11βHSD1 resulting in increased levels of active glucocorticoids in liver cells. Unlike liver cells, steroidogenic enzymes including 17β-hydroxysteroid dehydrogenase 3 (17βHSD3) forms the coupling with 11βHSD1. Thus the physiological concentrations of androstenedione serve as a substrate for 17βHSD3 utilizing NADPH to generate NADP+, which drives 11βHSD1 in Leydig cells primarily as an oxidase; thus eliminating the adverse effects of glucocorticoids on testosterone production. At the same time 11βHSD1 generates NADPH which promotes testosterone biosynthesis by stimulating 17βHSD3 in a cooperative cycle. This enzymatic coupling constitutes a rapid mechanism for modulating glucocorticoid control of testosterone biosynthesis. Under stress conditions, glucocorticoids also have rapid actions to suppress cAMP formation thus to lower testosterone production.